Dynamic analysis of a 10m diameter wind turbine rotor under maximum wind load of Malaysia - Mohd , Sofian (2006)
This project describes the application of finite element analysis (FEA) in studying the strength of the design of the wind turbine rotor under the wind speed of 36 m/s. The forces and pressure produced by the mentioned speed was initially estimated using Computational Fluid Dynamic (CFD). With the forces and pressure set as a boundary loads, the stress analysis was performed using Finite Element Method (FEM). The important criteria such as the displacement and factor of safety were considered in order to produce the optimized model of the wind turbine rotor. The optimized model was defined as the model with low maximum displacement and the minimum factor of safety of 1.5. As an option for cost effective design, the studies were also performed on the wind turbine model under the 15 m/s wind speed load. The model with the thinner AE2 blade (3mm thick) was found to be sufficient for the average wind speed of 15 m/s.